Determining the status of small dense low-density lipoprotein cholesterol level in women undergoing menopausal transition - Qingfang He; Yujia Fang; Lixin Wang; Mingbin Liang; Xiangyu Chen; Ruying Hu; Jieming Zhong (Frontiers in Endocrinology)
ObjectiveResearch on small dense low-density lipoprotein cholesterol (sdLDL-C) and menopausal status remains scarce. Our aim is to evaluate the relationship between serum sdLDL-C level and different menopausal status in a Chinese women population.MethodsIn 2022, a cross-sectional study was conducted including electronic standardized questionnaire surveys, anthropometric measurements, and biological specimen examinations based on communities. Permanent resident adults aged 30–69 years who lived in two communities in Zhejiang Province and participated in a community health examination from May 26 to September 17 were recruited. According to their menopausal status, the eligible women subjects were divided into premenopause, perimenopause, and postmenopause. Logistic regression model by SAS software was used to explore the association with sdLDL-C level and different menopausal status.ResultsA total of 2,062 women subjects were included with a median age of 57 (51, 63) years. There were 451 (21.9%) premenopause, 87 (4.2%) perimenopause, and 1,524 (73.9%) postmenopause women. The median sdLDL-C level was 0.937 (0.685, 1.209) mmol/L, and the sdLDL-C levels showed a gradually and significantly upward trend in premenopause, perimenopause, and postmenopause women, and this peaked in the postmenopause women. Logistic regression analysis showed that after controlling the confounding factors, compared with premenopause, postmenopause was significantly associated with increased sdLDL-C concentration (OR = 1.514, 95% CI: 1.025–2.238), while no significant association was observed either between serum sdLDL-C and perimenopause (compared with premenopause) or between serum sdLDL-C and postmenopause (compared with perimenopause).ConclusionsAn elevated sdLDL-C level was significantly associated with postmenopause and independent of chronological aging. The study supports that sdLDL-C is a promising risk biomarker for menopausal transition. Future studies should consider a broader population and a more rigorous and thorough study design to validate these findings.